Missouri Mathematics Project learning model with strategy Everyone is a Teacher Here to towards mathematical problem-solving and self-efficacy ability - Indah Resti Ayuni Suri; Agus Pahrudin; Ega Apriyana; Suherman Suherman (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2023)
Every student must acquire mathematical problem-solving skills and self-efficacy to assist them in the learning process and solve different mathematical problems. This study seeks to explore the impact of implementing “the Missouri Mathematics Project (MMP) learning model with the Everyone is a Teacher Here (ETH) strategy on the mathematical problem-solving skills and self-efficacy of learners”. This study employs a quasi-experimental design with a 2×2 factorial research scheme. In this research, tests of mathematical problem-solving skills and self-efficacy questionnaires were utilized to collect data. The method of data analysis employed the Normality test, the Homogeneity test, and the Multivariate Analysis of Variance (MANOVA) hypothesis tests. Based on the outcomes and MANOVA test calculations, it was determined that implementing the MMP learning model with the Everyone is a Teacher Here strategy affected students' mathematical problem-solving skills. The deployment of the MMP learning model with the Everyone is a Teacher Here strategy also affects students' self-efficacy. Implementing the MMP learning model with the Everyone is a Teacher Here strategy impacts learners' mathematical problem-solving skills and self-efficacy.